Organizational commitment, job satisfaction, job stress, psychological contracts and turnover intentions: assessing the role of social support - Retno Dwiyanti (2023)
The main objective of this study was to examine the relationship between job satisfaction and turnover intention, with social support as a moderating variable. The next objective is to examine the relationship between psychological contracts and turnover intention, with job satisfaction as a mediating variable. The relationship between organizational commitment and job stress is also the aim of this study. A quantitative approach with a survey method is used in this research. The population in this study were salespersons at retail companies in Purwokerto Indonesia, amounting to 979 people, and a total of 274 respondents were used as a sample in this study. The instruments in this study consisted of an organizational commitment questionnaire, a job satisfaction survey, a psychological contract scale, a work stress scale, a social support scale, and a turnover intention questionnaire. The results showed that there was a significant relationship between job satisfaction and turnover intentions with social support as a moderating variable ( = 0.081; t = 2.266; p < .01). While the relationship between psychological contracts and turnover intention with job satisfaction as a mediating variable is not significant ( = -0.043; t = 1.142; p > .05). The next result is that there is a significant relationship between organizational commitment, psychological contract, and job stress with turnover intention. The results of this study can be used by human resource managers to anticipate the exit of employees, especially salespeople from the organization. Through psychological contracts, organizations are more sensitive and understand how the expectations or desires of employees are in accordance with their beliefs about the organization. Companies can increase support from various parties to the sales force. The support felt by the salesperson from all parties can result in job satisfaction so that the salesperson's desire to leave his job can be avoided.